Penerapan Pembelajaran Tematik Kurikulum 2013 oleh Guru SD/MI di Desa Klepek Kecamatan Sukosewu Kabupaten Bojonegoro Semester Gasal Tahun Ajaran 2014/2015 - Ari Indriani (Jurnal VARIDIKA, 2015)
Elementary school is the starting point of formal education in Indonesia. While this study has the objective to provide insight to the teacher on the application of thematic learning curriculum 2013 that includes planning, implementing and assessing thematic learning curriculum in 2013. Thematic learning curriculum 2013 that applicable in elementary school / MI is an integrated thematic learning, learning to integrate material from multiple subjects in a single theme to cultivate a skill on learners. The subjects in this study are teachers in elementary school / MI in Klepek Sukosewu District of Bojonegoro and methods of data collection use interviews and questionnaires. The conclusion from this study is that the learned predetermined theme of the center located at Master Books, learning methods used according to the theme being studied, while the valuation techniques used are based on attitude.